ANALISIS KANDUNGAN ZAT WARNA METHANYL YELLOW PADA TAHU KUNING YANG BEREDAR DI KECAMATAN SAMARINDA ULU DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Cristina, Atika; Linden, Susana; Leswana, Nurillahi Febria (Jurnal Farmasi Etam (JFE), 2024)
Research on methanyl yellow dye in yellow tofu was carried out to determine the presence or absence of methanyl yellow and to determine the levels of methanyl yellow in yellow tofu samples circulating on the market in Samarinda Ulu sub- district by Thin Layer Chromatography and UV-Vis Spectrophotometry. This study began with a TLC test on 10 samples of yellow tofu so that the results obtained after the test obtained a standard Rf value of 0.946 while in the 10 samples of yellow tofu, the presence of methanyl yellow dye was not identified. In the UV-Vis Spectrophotometry test, the maximum wavelength was 422 nm with an absorbance of 0.279, which is still within the standard range for the maximum wavelength of methanyl yellow, namely 390-450 nm. The standard curve equation results obtained are y = 0.1062x – 0.0719 with a correlation coefficient (r) of 0.9989, this indicates that the correlation is very strong if the R2 value obtained is above 0.9 but less than 1.0. The UV-Vis spectrophotometry method was also carried out on 10 samples of yellow tofu although it had been tested using the thin layer chromatography method and did not identify the presence of methanyl yellow dye. The aim was to see the wavelength produced by each sample along with its absorbance value.